Is grade retention the solution for failing? - Prieto-Latorre, Claudia; López-Agudo, Luis Alejandro; Marcenaro-Gutiérrez, Óscar David (My University, 2020)
The convenience of grade retention for students’ adequate progression in the education system has been the focus of great debate. However, the characteristics that the grade retention variable presents when explaining students’ academic achievement has prevented most of the research works to delve into the effect of this policy. Because of that, in the present research work we intend to get as close as possible to endogeneity free estimate by the use of rich census and longitudinal data, together with a student fixed-effects within students between-academic years strategy. We find that grade retention affects students’ academic performance. Autores: Luis Alejandro Lopez-Agudo, Claudia Prieto Latorre, Oscar David Marcenaro-Gutierrez Palabras clave: grade retention, repetion, academic performance.
Keywords: Rendimiento académico; Grade retention; Repetition; Academic performance